Interpretation of the Meaning of the Term Islam in Al-ManÄr Tafsir and Its Relationship to Inter-Religious and Inter-Cultural Relations - Saifullah, Saifullah (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
This article examines the interpretations of “al-IslÄm” and its effects on inter-religious and intercultural relationships. It focuses on al-Manar's interpretation of the terms